Unusual Radiographic Presentation of a Dentigerous Cyst with Inverted Impacted Molar: A Case Report Study type: A Case report - Chauhan, Himanshu; Tandon , Sapna; Singh, Sreyas; Chatterjee, Dipanjan; Mehra , Hemant; Hazra, Swastik (Journal of Neonatal Surgery, 2025)
Background: Dentigerous cyst, a type of developmental odontogenic cyst, one of the most common one of its kind, forms around the crown of an unerupted or an impacted tooth. It develops due to fluid accumulation between the reduced enamel epithelium and the tooth's crown, typically attaching at the cementoenamel junction. These cysts are usually asymptomatic unless infected, and are often discovered during routine radiographic examinations. Case Presentation: This report presents a case of a 58 years old male patient with an impacted third molar in his right lower back region of the jaw. The patient presented with a complaint of a pain in the right lower back region of the jaw. The pain has been present for approximately 6 months, with no gross deformity to the lower jaw bone. On radiographical examination, an inverted 48 was seen in association with a dentigerous cyst, enclosing the coronal portion of the tooth extending up to 2/3rd portion of the root. The patient reported no associated symptoms, such as discharge. Enucleation was carried. Conclusion: Although Dentigerous cysts doesn’t have the tendency of reappearance, this does not excludes the need for a thorough regular check-up at every follow-up. In conclusion, the histopathologically proven and an non-complicated healing of the wound is the only reassurance for the patient’s recovery